WOOD RESIDUES FROM AMAZON SPECIES FOR THE PRODUCTION OF PELLETS - COSTA NETO, ANTONIO ALBERTO DA; Hillig, Everton; Souza, Marcelo José Raiol; Jaily Kerller Batista de Andrade, Jaily Kerller Batista de; Garrett, Alexandre Techy de Almeida; Bednarczuk, Ezaquel (Floresta, 2025)
The objective of the work was to produce pellets from deck and flooring waste and evaluate their quality using the ISO 17225-2 standard. Wood residues from the species Handroanthus serratifolius (Vahl) S. Grose (yellow ipe), Hymenaea courbaril L. (jatobá), Manilkara elata Huber (maçaranduba), Dinizia excelsa Ducke (angelim stone), Astronium lecointei Ducke (muiracatiara) and Pinus taeda L., the species currently most used in pellet production in Brazil. The production of pellets was carried out in an Amandus Kahl model 14-175 laboratory pelletizer. The parameters evaluated were diameter, length, moisture content, unit density, bulk density, mechanical durability, fines content, volatile and fixed carbon content, ash content, higher and net calorific value, and energy density. The results obtained for the 7 types of pellets produced met the regulatory requirements for residential, commercial, and industrial use, emphasizing the bulk density above the parameters positively influencing the energy issue. Among the species, there was an emphasis on yellow ipe wood, which presented higher calorific value values ​​of 20.18 MG/kg, as well as a net calorific value of 17.17 MJ/kg and energy density of 13.93 GJ/m³.